Vegetable brassicas and related crucifers - Dixon, G. R.; Dixon, G. R. (Wallingford :CABI, 2006)
This book identifies the scientific principles underpinning crop production in Western (Occidental) brassicas derived from Brassica oleracea and Oriental types derived from B. rapa [B. campestris], Chinese cabbage and its relatives. It examines: plant breeding; the potential for genetic manipulation; model forms in Arabidopsis thaliana and Wisconsin Fast Plants®, seeds and seedlings; developmental physiology and yield prediction; crop agronomy; sustainable, ecologically integrated approaches to controlling competition for resources from pathogens, pests and weeds; crop quality; physiological disorders; and contributions to human health and welfare. It is of value to professionals, producers and students in horticulture, plant science, plant breeding, physiology, pathology and entomology, ecology, sustainable cropping systems and food quality.
Keywords: FF020 - Plant Breeding and Genetics; FF060 - Plant Physiology and Biochemistry; FF100 - Plant Production; FF500 - Weeds and Noxious Plants; FF610 - Viral, Bacterial and Fungal Diseases of Plants, (New March 2000); FF620 - Plant Pests, (New March 2000); FF700 - Plant Disorders and Injuries (Not caused directly by Organisms); QQ050 - Crop Produce; QQ500 - Food Composition and Quality; WW100 - Genetic Engineering, Gene Transfer and Transgenics, (New June 2002)